Immersion into Mathematics Instruction: An Ethnography on the Development of Problem-Solving Skills by Homogenized Grade 10 Learners - Cerbito, Jury (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the development of mathematical problem-solving skills among homogenized Grade 10 learners of Ramon Magsaysay Cubao High School through immersion in mathematics instruction, considering both teacher and learner perspectives. Anchored on theories related to classroom management, social cognitive learning, self-regulated learning, cognitive load, constructive alignment, and educational effectiveness, the study employed a qualitative ethnographic research design. Data were gathered through classroom observations, semi-structured interviews with four Grade 10 mathematics teachers, focused group discussions with twenty selected learners, lesson plan analysis, and field notes involving approximately 150 learners from four homogenized classes. The findings revealed that mathematics instruction was generally structured, MELC-aligned, and supported by step-by-step explanations, guided practice, questioning, peer interaction, and teacher modeling. However, problem-solving development was limited by fast pacing, formula confusion, anxiety, time pressure, mental blocking, and dependence on teacher or peer support. Learners commonly used strategies such as rereading problems, consulting examples, asking classmates or teachers, using trial-and-error, and seeking digital support. Across immersion cycles, clinical supervision helped teachers improve questioning, pacing, differentiation, conceptual integration, and classroom support, resulting in better learner engagement and gradual improvement in problem-solving participation. The study concludes that strengthening problem-solving skills requires a balance between procedural clarity, conceptual reasoning, emotional support, differentiated instruction, and sufficient thinking time. The study supports SDG 4, Quality Education, by focusing on improved mathematics instruction and learning outcomes, and SDG 10, Reduced Inequalities, by examining learning opportunities across homogenized class groupings. Its sustainability impact lies in promoting educational, institutional, and equity-oriented improvements through responsive teaching, instructional supervision, and inclusive mathematics support.